Редкое сочетание перфоративной язвы двенадцатиперстной кишки и острого гангренозного аппендицита - Капшитарь, А.В. (Таврический медико-биологический вестник, 2012)
Представлене досить рідкісне сполучення перфоративної виразки дванадцятипалої кишки (ПВДПК) та гострого гангренозного апендициту (ГГА), що склало 0,8% із 132 пацієнтів з перфоративною гастродуоденальною виразкою , оперованих у клініці за останні 10 років. Шпиталізований з діагнозом «Перфоративна виразка шлунка? Гострий панкреатит?». Показання до операції встановлені за результатами проби Хенельдта. На лапаротомії діагностовано ПВДПК та ГГА. Висічення ПВДПК з пілоропластикою за Джаддом-Хорслі і ваготомія за Бурже, назо-еюнальний зонд, апендектомія. A rare combination of perforated duodenal ulcer (PDU) and acute gangrenous appendicitis (AGA), which accounted for 0.8% of 132 patients with perforated gastroduodenal ulcer, has been operated in clinic over the past 10 years. Hospitalized with a diagnosis of “Perforated duodenal ulcer? Acute pancreatitis?” Indications for surgery were based on the Heneldt test results. Laparotomy showed PDU and AGA. Excision of PDU was performed with pyloroplasty by Judd-Horsley method, and vagotomy was done by Bourqe method, with use of the nasoejunal probe and appendectomy